Incidence and Risk Factors of Neonatal Hypoglycemia During the First 48 Hours of Life in a Tertiary Level Hospital - Hassan, Md Kamrul; Pervez, Abu Faisal Md; Biswas, Rajib; Debnath, Shuvo; Syfullah, Khalid Ahmed (Faridpur Medical College Journal, 2020)
Neonatal hypoglycemia is one of the common metabolic problems causing neonatal mortality and neurodevelopmental impairments. In developing countries, where the classic risk factors for neonatal hypoglycemia prevail; understanding the prevalence and association of hypoglycemia in different settings is essential. Our aim of this study was to identify the incidence and associated risk factors that predicted the occurrence of neonatal hypoglycemia during the first 48 hours of life. This hospital-based prospective case-control study was undertaken in the Department of Pediatrics in Faridpur Medical College Hospital, Bangladesh; from June 1, 2019 to July 31, 2019. Blood glucose levels of all the admitted newborns were noted on two occasions at 24 hours apart. Hypoglycemic neonates were selected as case and 3 euglycemic neonates for each case with similar age and sex were selected as control. Clinical characteristics of the mother and the baby were analyzed statistically in relation to the occurrence of hypoglycemia. We have found the incidence of neonatal hypoglycemia was 17.2%. Prematurity, low birth weight, small and large for gestational age, perinatal asphyxia, hypothermia, and delay in the initiation of breast feeding were significant neonatal factors. Maternal factors such as gestational diabetes mellitus, eclampsia, and fever during delivery had strong association as well. Understanding the incidence and risk factors may help prompt identification of hypoglycemic baby may also help to take early and effective measures to prevent the sequels of neonatal hypoglycemia. Faridpur Med. Coll. J. Jan 2020;15(1): 12-15